2015
DOI: 10.1016/j.ecss.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Photo-regulation in microphytobenthos from intertidal mudflats and non-tidal coastal shallows

Abstract: International audienceThe study investigated seasonal changes in the photo-regulatory mechanisms of microphytobenthosfound in intertidal mudflats (Aiguillon Bay, the Atlantic, France) and non-tidal sandy coastal shallows(Puck Bay, the Baltic, Poland) based on photosynthetic pigment characteristics and the estimates ofphotosynthetic parameters obtained through oxygen evolution measurements. The intertidal communitiesconsisted of motile diatom species typical of epipelon. The non-tidal microphytobenthos wascompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“…In contrast, an epipelic species, Seminavis robusta, shows a less dynamic NPQ, despite concerted de novo synthesis of both Dtx molecules and LHCX proteins. Our findings add to the physiological underpinning of the differential response of motile and non-motile diatom species Juneau et al 2015) and of benthic diatom communities in sediment Pniewski et al 2015;Cartaxana et al 2016b) to their environment.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, an epipelic species, Seminavis robusta, shows a less dynamic NPQ, despite concerted de novo synthesis of both Dtx molecules and LHCX proteins. Our findings add to the physiological underpinning of the differential response of motile and non-motile diatom species Juneau et al 2015) and of benthic diatom communities in sediment Pniewski et al 2015;Cartaxana et al 2016b) to their environment.…”
mentioning
confidence: 66%
“…While our knowledge of NPQ regulation is mostly based on studies of planktonic diatoms, whose light climate is mostly governed by water column turbulence, far less attention has been paid to NPQ regulation in benthic diatoms thriving in, and on, the sediments of intertidal flats (Jesus et al 2009;Perkins et al 2010;Cartaxana et al 2011Cartaxana et al , 2016aSerôdio et al 2012;Lavaud and Goss 2014;Ezequiel et al 2015;Laviale et al 2015;Pniewski et al 2015). Like terrestrial plants, these diatoms can experience fast light fluctuations, not buffered by a water column, during low tide.…”
mentioning
confidence: 99%
“…The curves were plotted on the basis of laboratory results (Clark oxygen electrode measurements) using the equation of Jassby and Platt (1976). According to a photoacclimation model description (Prezelin, 1981;Prezelin and Sweeney, 1979;Ramus, 1981;Richardson et al, 1983;Pniewski et al, 2015), the results of the present study indicated changes in photosynthetic unit (PSU) sizes as the photoacclimation mechanism, which occurred most frequently (Table 1). There were also P − E curves pointing to some changes in enzymatic reactions and the altering of accessory pigments' activity.…”
Section: Photosynthesismentioning
confidence: 83%
“…The MPB biofilm faces strong daily and seasonal variations of mud surface temperature (MST) caused by heating through solar irradiance during low tide exposure periods (Harrison and Phizacklea, 1985;Harrison, 1985;Guarini et al, 1997) and develops phenological adaptations. Blanchard and Cariou-Le Gall (1994), Barranguet et al (1998) and Pniewski et al (2015) 20 showed a light-related seasonal adjustment of photosynthetic parameters (the photosynthetic capacity P b max and the light saturation parameter E k ) from Production-Irradiance (P-E) curves fitted on the model of Platt and Jassby (1976). Photoinhibition was rarely observed in the field since epipelic diatoms can achieve "micro-migrations", i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The light saturation parameter corresponds to the irradiance at which photosynthesis switches from light reactions (light absorption and photochemical energy conversion) to dark reactions (reductant utilization) (Sakshaug et al, 1997). It has been reported to vary seasonally in benthic microalgae (Blanchard and Cariou-Le Gall, 1994;Barranguet et al, 1998;Light and Beardall, 2001;Pniewski et al, 2015;. Cells increase their light saturation parameter at 10 high irradiance (summer) and reduce it with decreasing light levels (Sakshaug et al, 1997).…”
mentioning
confidence: 99%